At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
Step-by-step explanation:
2^3 . 2^- 5 . 2^- 1
= 2^( 3 - 5 - 1 )
= 2^( 3 - 6 )
= 2^- 3
= 1 / 2^3
= 1 / 8
If
2 . 2^3 . 2^- 5 . 2^- 1
= 2^1 . 2^3 . 2^- 5 . 2^- 1
= 2^( 3 - 5 - 1 + 1 )
= 2^( 3 - 5 )
= 2^- 2
= 1 / 2^2
= 1 / 4
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.